T‐bet as a key regulator of mucosal immunity. Issue 4 (23rd February 2016) - Mohamed, Rami; Lord, Graham M.
Summary: Initially understood to be a key regulator of interferon‐ γ ‐producing helper T cells, our knowledge of T‐bet's functional roles has expanded to encompass a growing range of cellular lineages. In addition to regulating other interferon‐ γ ‐producing adaptive immune cells, it is now clear that T‐bet plays a fundamental role in the regulation of innate immune responses across mucosal surfaces. This homeostatic role is demonstrated by the spontaneous colitis that occurs when T‐bet is deleted from innate immune cells in RAG −/− mice. Using this model as a focal point, we review our understanding of T‐bet's regulation of adaptive and innate immune systems, focusing particularly on mucosal populations including innate lymphoid cells, dendritic cells and intraepithelial lymphocytes. With the increasingly diverse effects of T‐bet on different lineages, the classical binding‐centric paradigm of T‐bet's molecular functionality has increasingly struggled to account for the versatility of T‐bet's biological effects. Recent recognition of the synergistic interactions between T‐bet and other canonical transcription factors has led to a co‐operative paradigm that has provided greater explanatory power. Synthesizing insights from ChIP‐seq and comparative biology, we expand the co‐operative paradigm further and suggest a network approach as a powerful way to understand and model T‐bet's diverse functionality.